A Provincial View of Economic Integration - Klein, Michael (IMF Working Papers; Working Paper, 1997)
This paper develops a method of testing levels of economic integration based upon consumption smoothing, and tests it using data on trade balances across Canadian provinces. The results indicate the provinces are highly integrated within Canada, but integration between Canada and the rest of the world is partial. Provincial trade balances respond only about half as much to events in the rest of the world as they do to events within Canada. In short, national borders appear to matter for intertemporal trade.